EFFECT OF MYOFASICAL RALEASE VERUS SPECIFIC INFERIOR CASPULAR STRTCH IN FROZEN SHOULDER PATIENTS - Mohite, Shraddha; Rayjade, Amrutkuvar; Khilwani, Amruta; Nikam, Gauri (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND: The shoulder joint is the most mobile joint in the human body. The joint structure around the shoulder is capsule, disk, ligament, bursae, glenoid labrum, and muscle. The most common structure affected in frozen shoulder is the inferior joint capsule because the inferior capsule is thin and deficient for the passage of the long head of the biceps. Methods: An experimental study was conducted at Krishna College of Physiotherapy, Karad. 46 participants in the age group of 40-70 years of both genders were selected according to the inclusion criteria. Group A (23 participants) was treated with myofascial release along with exercises, while Group B (23 participants) was treated with specific inferior capsular stretch along with exercises. Then the statistical analysis was done between the two groups to find the result. Results: Out of 46 selected subjects. Statistical analysis was done using paired and unpaired t-tests. The pre- and post-assessment was done among Group A and Group B. . It was observed that there was statistical significance with 0.5. The mean difference among VAS and variables among Group B was more as compared to Group A. Hence, we had proved that Group B was better than Group A. Conclusion: Thus, from the conducted study, it concludes that specific inferior capsular stretch had significant improvement clinically and statistically compared to myofascial release on SPADI, VAS, and ROM scores, thus facilitating functional outcomes.